ANALISIS KERENTANAN BENCANA BANJIR DI KABUPATEN BOLAANG MONGONDOW UTARA - Pontoh, Muh Reza Novian; -, Sangkertadi; Tilaar, Sonny (SPASIAL, 2021)
The natural disasters in Indonesia have tended to increase over the years, flood disasters will occurthroug hout the country. The increasing level off lood disasters in Indonesia does not only affect thearea,but the amount of damage that is caused is also increasing. The research location in Bolaang Mongondow Regency for floodv ulnerability.TheobjectivesofthisresearchareidentifyingFloodTeachingCallsinBolaangMongondow Utara Regency and recommending flood disaster mitigation strategies to reduce flooddisaster lottery drawings. The methodsconducted by quantitative descriptive analysis method and overlay, in which too obtain vulnerability data that combine son aflood vulnerability vulnerability to social vulnerability, physical vulnerability, economic vulnerability, and environmental vulnerability. The resultsof this study are the level of flood vulnerability in Bolaang Mongondow Utara Regency isclassified into three, namely high, medium and low, Further, the results of the analysis of the flood disastervulnerability index for 2 sub-districts with high levels of vulnerability need to be carried out by an institution or recommendation for the North Bolaang Mongondow Regency government related to disaster mitigation planning and development based on physical, social, economicand environmental aspects.Â keyword:Disaster,Flow,vulnerability,disastermitigation,mapping